Composition en éléments azotés minéraux et organiques dissous de l'eau du bassin conchylicole de Marennes-Oléron - Heral, Maurice; Robert, Jean-michel; Truquet, Isabelle; Barbaroux, Olivier; Garnier, Jacqueline; Razet, Daniel (Council Meeting, 1981, of the International Council for the Exploration of the Sea, (Woods Hole, MA (USA)) (5 Oct 1981), 1981)
Values of nitrogen nutrients (ammonia, nitrite and nitrate) are compared with values of total organic nitrogen and urea. In summer, the consumation by micro and macrophytes is added to less important telluric input of nineral nitroge. However, an important provision of organic nitrogen remains. On the contrary, in winter, organic nitrogen does not represent more than 10% of total nitrogen. The autors postulate that populations of oysters are at the starting point of the organic nitrogen production cycle. Les teneurs en sels minéraux azotés (ammoniaque, nitrites et nitrates) sont comparées aux teneurs en azote organique total et en urée. En été, à la moindre importance des apports telluriques en azote minéral s'ajoute la consommation par les micro et macrophytes cependant une importante réserve d'azote organique subsiste. Par contre, en hiver, l'azote organique ne représente que 10% de l'azote total. Il est postulé que les populations d'huîtres sont à l'origine du cycle de production d'azote organique.